From Sea to Shining Sea - Bronson, AA; Blouin, René; Gale, Peggy; Lewis, Glenn (Toronto : The Power Plant, 1987)
Askevold, David ; Brousseau, Napoleon ; Baird, Rebecca ; Baxter, Iain ; Borduas, Paul-Emile ; Britton, Susan ; Buchan, David ; Cameron, Eric ; Campbell, Colin ; Craig, Kate ; Cruise, Stephen ; Dean, Tom ; General Idea ; Lebredt, Gordon ; Lewis, Glenn ; Massey, John ; Meigs, Sandra ; Metcalfe, Eric ; Murray, Ian ; Neil, Al ; Racine, Rober ; Steele, Lisa ; Storey, Alan ; Waterman, Doug ; Watt, John ; Werden, Rodney
From Sea to Shining Sea, the Power Plant, Toronto, 26 June - 19 Aug. 1987
English
kunstcatalogus